Analisis Politik Keuangan Daerah di Era Desentralisasi Studi Akuntabilitas Kebijakan â€œProgram Banjar Cerdasâ€ di Kota Banjar tahun 2013 - Ramdani, Deni Fauzi (Sawala : Jurnal Administrasi Negara, 2016)
This research aims to analyze the Policy of Smart Banjar Program (SBP) as a pro  public-budget policies implemented in Banjar city  is a political model that comes after the local financial decentralization. Measuring with the accountability studies expected to find new local political dynamics in the contestation will be the mapping of budgeting and budgeting mechanism to buget review in a decentralized system that is more complex than the previous era. Studies accountability in the process of formulating and implementing policy seen from the distribution of local budgets in accordance with the implementation of Good Governance within the framework of local autonomy is an important study. Because of the budget is driven not only be done in a democratic for formulating process, but also should be more pro-poor and pro improvement of human development indicators. The lack of  public  accountability policy which could be involved in monitoring and evaluation. In this space included in assessing public policies  that are being implemented. Public  know the outcome, impact or implications of policies being implemented. The important part is expected in public accountability is the need review and reform on this policy in terms of free education through SBP in the peride 2013. Using the  analytical tool  from David Easton is combined  JD Stewart that accountability identifies five levels: Policy Accountability as accountability for policy choices are made; Accountability Program as the accountability for the achievement of objectives / outcomes  and effectiveness are achieved; Performance accountabilty as accountability towards the achievement of efficient activity; Process accountabilty as accountability for the use-process, procedure, or a decent size in implementing measures adopted; Probity and legality Accountability as accountability for legality and honesty of the use of funds in accordance with approved budgets or obedience to the laws in force. The methode Based on a qualitative approach uses a type of descriptive with case study. Accountability mechanism from any process of accountability in SBP policy in Banjar in 2013 are still experiencing a gap in minimizing accountability so that the process is less transparent, effective and efficient. SBP policies still biased by political interests ahead of the elections (pilkada) of 2013. In addition, elements of society, NGOs, Banjar community in general who became the subject of accountability does not get valid data and information so that accountability externally inadequate.